Borrowing non-canonical inverse between Kabardian and Abaza. (July 2021) - M. Arkadiev, Peter
Abstract : Abaza, a polysynthetic ergative Northwest Caucasian language, shares with its neighbour and distant relative Kabardian a typologically peculiar use of the deictic directional prefixes monitoring the relative ranking of the subject and indirect object on the person hierarchy. In both languages, the cislocative ('hither') prefixes are used if the indirect object outranks the subject on the person hierarchy, and the translocative ('thither') prefixes are used in combinations of first person subjects with second person singular indirect objects. This pattern, reminiscent of the more familiar inverse marking and hence called 'quasi-inverse', is observed with ditransitive and bivalent intransitive verbs and is almost fully redundant, since all participants are unequivocally indexed on verbs by pronominal prefixes. I argue that this isogloss, shared by West Circassian (a close relative to Kabardian) but not with Abkhaz, the sister-language of Abaza, is a result of pattern replication under intense language contact, which has led to an increase of both paradigmatic and syntagmatic complexity of Abaza verbal morphology.